2016
DOI: 10.1186/s40064-016-3165-6
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric profile of the global scientific research on autism spectrum disorders

Abstract: Background: Autism spectrum disorders (ASD) are a group conditions classified as neuro-developmental disorders. Research activity on ASD is important for all countries since such disorders have both social and health consequences. The objective of this study was to analyze research output on ASD during the period 2005-2014. Methods:All articles relevant to ASD plus all articles published in autism journals were retrieved using Scopus database. VOSviewer software was used to create density and network visualiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 46 publications
1
50
0
5
Order By: Relevance
“…Outbreaks of emerging viral infectious diseases have been commonly reported from many countries in Africa, Asia, and Africa [52,[57][58][59][60][61][62]. For example, MERS-CoV and Crimean-Congo fever have been reported in more than 20 countries, mostly in Asia, Africa, and Middle East [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]. The outbreaks of SARS in Hong Kong and China had a great economic and public health impact [78][79][80].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outbreaks of emerging viral infectious diseases have been commonly reported from many countries in Africa, Asia, and Africa [52,[57][58][59][60][61][62]. For example, MERS-CoV and Crimean-Congo fever have been reported in more than 20 countries, mostly in Asia, Africa, and Middle East [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77]. The outbreaks of SARS in Hong Kong and China had a great economic and public health impact [78][79][80].…”
Section: Discussionmentioning
confidence: 99%
“…Development of a new vaccine for the prevention of Lassa fever [126] 2005 PLoS Medicine 115 These limitations and others are found in most bibliometric studies [71,[87][88][89][90][91]. This study focused only on the top eight emerging infectious diseases expected to cause severe outbreaks in the near future.…”
mentioning
confidence: 99%
“…Several bibliometric studies on various medical topics concluded that the USA ranked first in research productivity [39, 40, 5153]. However, it was surprising that most active authors were either French or Japanese and none were Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the choice of Scopus was based on the understanding of the authors that it is the largest and most comprehensive database [36]. Furthermore, Scopus has been previously used in many published bibliometric studies [37][38][39][40][41][42].…”
Section: Methodsmentioning
confidence: 99%
“…Our study has few limitations that need to be considered when interpreting the results. Like all bibliometric studies [38,39,42,[106][107][108][109], false positive and false negative results are unavoidable because there is no perfect and comprehensive research query. Therefore, we might have missed some articles either due to search query or to the use of title search rather than title/abstract search.…”
Section: Type Of Documentmentioning
confidence: 99%